Theory and Practice of Modern Antenna Range Measurements Volume 2 - Parini, Clive; Gregson, Stuart Fraser; McCormick, John (Lead radar systems engineer); Van Rensburg, Daniël Janse; Eibert, Thomas (SciTech Publishing, an imprint of The Institution of Engineering and Technology, 2020)
This two-volume book provides a comprehensive introduction and explanation of both the theory and practice of all forms of modern antenna measurements, from basic assumptions to detailed application scenarios.
Pagination continues from volume 1; volume begins with chapter 8
Keywords: Antennas (Electronics); Antenna radiation patterns.; Electromagnetic fields.; Electromagnetic theory.; elektronické knihy; electronic books